Justice Without Teeth: The Illusion of International Accountability in the Rohingya Crisis - Ananda Felix Mursito (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2026)
Violence against the Rohingya community in Myanmar has emerged as one of the most systematic and brutal humanitarian tragedies in contemporary history. Amidst the realities of genocide, crimes against humanity, and forced deportation, international law faces an acute challenge in demonstrating its normative and operational reach. This article aims to provide a philosophical and juridical analysis of the international legal constellation surrounding the crimes committed against the Rohingya ethnic group, the responsibility of the State of Myanmar, and the failure of the international community to uphold the principles of justice. This study employs a normative-juridical method using both conceptual and case-based approaches, and it critically examines international legal norms such as the Rome Statute, the 1948 Genocide Convention, the principle of jus cogens, and the doctrine of erga omnes obligations. The analysis reveals that the crimes committed against the Rohingya community constitute not only grave violations of fundamental norms of international law but also reflect a collective failure of the global community in fulfilling its responsibilities. Moreover, the study identifies a stagnation in the enforcement of legal accountability, rooted in political factors, institutional weaknesses, and the normalization of diplomatic relations. The article recommends strengthening transnational mechanisms and establishing an ad hoc tribunal as necessary measures for the restoration of substantive justice for victims and for reaffirming the supremacy of international law over impunity.